Early outcome of adult cardial surgery in low volume community hospital experiences of young surgeon from developing country - Sembiring, Yan Efrata (Folia Medica Indonesiana, 2017)
After finishing training, every young cardiac surgeon wants to start a good carrier as fast as they can. We describe the early outcome of adult cardiac surgery that have been done by a young in low volume community hospital in Surabaya – Indonesia within periods December 2010 – December 2013. A retrospective study of 133 adult cardiac cases during December 2010 – December 2013 at Division of Thoracic, Cardiac and Vascular Surgery Dr. Soetomo Hospital Surabaya provides a comprehensive data concerning adult cardiac procedures which collected and analyzed. In last 3 years, the total number of adult cardiac disease which is undergone a surgery was 133 cases. The procedures were involved CABG (85 cases, 63.91%); valve procedures (7 cases, 5.26%); and others procedures (6 cases, 4.51%). All cases were done by a young surgeon. Thirty day early follow up, there were 3 patients suffered from wound infection, 7 patients undergone re-do procedures due to mediastinal bleeding and cardiac tamponade. Mortality rate was 1.5%. The conclusion, good mentoring from senior surgeon and good training give a good result of adult surgery done by a young surgeon in low volume community hospital.